THE EVALUATION OF THE IMPLEMENTATION OF NATIONAL EDUCATION STANDARDS ON ANTECEDENT COMPONENTS IN SPECIAL OF VOCATIONAL HIGH SCHOOL - Ema Noviah; Wardani Rahayu (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2020)
The children's Special Correctional Institution (LPKA) on Tangerang City is one of the institutions that organizes the form of coaching Vocational High School (SMK). Implementation of education in Vocational High School must meet the minimum criteria in accordance with national education standards. Learning planning, educator qualifications and infrastructure is one of the components that exist in the national standard of education. This research aims to evaluate the quality of Lesson Plan (RPP) and assessment, educator qualifications, and infrastructure in the antecedent component of the Concatenate stake model in Special of Vocation High School. This research is an evaluative research with a qualitative approach. The method of data collection used in the form of interviews, documentation studies, and observations with the validity technique of data research results using the credibility by prologue engagement, persistent observation, and member checking. The results showed that educators first did not prioritize Learning Program Planning and its assessment, both lacking facilities of learning infrastructure, and all three educators who did not have a certificate of educators. Keyword: Antecedent component, evaluation, the children's Special Correctional Institution (LPKA)